2023
DOI: 10.3389/fmars.2023.1186809
|View full text |Cite
|
Sign up to set email alerts
|

Chondrinema litorale gen. nov., sp. nov., of the phylum Bacteroidota, carrying multiple megaplasmids isolated from a tidal flat in the West Sea, Korea

Abstract: A Gram-stain-negative, long rod, oxidase and catalase-positive strain WSW3-B12T was isolated from red algae on tidal flats in the West Sea, Korea. Phylogenetic analysis based on the 16S rRNA gene sequence revealed that the strain WSW3-B12T had the highest sequence similarity, 92.7%, to Flexithrix dorotheae DSM 6795T, followed by Rapidithrix thailandica TISTR 1750T at 90.8% in the family Flammeovirgaceae of the phylum Bacteroidota. The whole genome sequence determined using both the Nanopore and Illumina platfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 94 publications
0
4
0
Order By: Relevance
“…Motility was observed by using a hanging-drop technique, and gliding activity was observed by growing the strain on low-nutrient media composed of sea water and 0.7% (w/v) agar ( Tittsler and Sandholzer, 1936 ). The optimal temperature and salt tolerance for the growth was determined by using MA ( Muhammad et al, 2022 ) while the optimal pH for the growth was tested in MB ( Muhammad et al, 2023 ). To determine the growth under an anaerobic condition, all three strains were tested on a solid medium composed of 0.2% (w/v) glucose, 2% (w/v) NaCl, 0.1% (w/v) polypeptone, 0.1% (w/v) KH 2 PO 4, 0.1% (w/v) K 2 HPO 4 , 0.2% (w/v) NH 4 Cl, 0.14% (w/v) MgSO4, NaNO 3 (w/v) 0.17, 1.5% (w/v) agar, 0.1% (w/v) resazurin, 0.05% (w/v) cysteine HCl, 1 mL trace elements, and 1 mL multivitamins ( Wolin et al, 1963 ; Kim et al, 2001 ; Bae et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Motility was observed by using a hanging-drop technique, and gliding activity was observed by growing the strain on low-nutrient media composed of sea water and 0.7% (w/v) agar ( Tittsler and Sandholzer, 1936 ). The optimal temperature and salt tolerance for the growth was determined by using MA ( Muhammad et al, 2022 ) while the optimal pH for the growth was tested in MB ( Muhammad et al, 2023 ). To determine the growth under an anaerobic condition, all three strains were tested on a solid medium composed of 0.2% (w/v) glucose, 2% (w/v) NaCl, 0.1% (w/v) polypeptone, 0.1% (w/v) KH 2 PO 4, 0.1% (w/v) K 2 HPO 4 , 0.2% (w/v) NH 4 Cl, 0.14% (w/v) MgSO4, NaNO 3 (w/v) 0.17, 1.5% (w/v) agar, 0.1% (w/v) resazurin, 0.05% (w/v) cysteine HCl, 1 mL trace elements, and 1 mL multivitamins ( Wolin et al, 1963 ; Kim et al, 2001 ; Bae et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…While investigating the microbial diversity of the tidal flats in the West Sea, Korea, a high number of novel bacteria capable of degrading complex polysaccharides were isolated ( Muhammad et al, 2023 ; Nguyen et al, 2023 ). Three novel strains, ABR2-5 T , BKB1-1 T , and WSW4-B4 T , were isolated from macroalgae and sea mud.…”
Section: Introductionmentioning
confidence: 99%
“…All isolates were checked for gliding motility through the hanging-drop technique and using soft agar media [27]. The optimum temperature and salt concentration for growth were assessed by using MA as the growth medium [2], while the optimum pH was examined using pH adjusted marine broth (MB, BD) as the testing medium [28]. For the determination of growth under anaerobic conditions, all isolates were inoculated within an anaerobic chamber (Coy Labs, USA) and the cells were cultivated on MA in an anaerobic jar at 30 °C (BD GasPak Systems).…”
Section: Physical Biochemical and Chemotaxonomic Analysismentioning
confidence: 99%
“…After Pseudomonatoda and Cyanobacteria, members of the phylum Bacteroidota rank as the ocean's most abundant bacterial group [1]. Bacteroidota strains have been isolated from a wide range of marine environments, including tidal flats [2], coastal sediments [3], deep sea [4], and hydrothermal vents [5]. By analyzing metagenomic data obtained from global ocean sampling and conducting a CARD-FISH study across the North Atlantic Ocean it was revealed that, subsequent to Cyanobacteria and Pelagibacter, Bacteroidota are the prevailing bacteria in marine environments [6].…”
Section: Introductionmentioning
confidence: 99%